2021
DOI: 10.3390/foods10081827
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolizidine Alkaloids in the Food Chain: Is Horizontal Transfer of Natural Products of Relevance?

Abstract: Recent studies have raised the question whether there is a potential threat by a horizontal transfer of toxic plant constituents such as pyrrolizidine alkaloids (PAs) between donor-PA-plants and acceptor non-PA-plants. This topic raised concerns about food and feed safety in the recent years. The purpose of the study described here was to investigate and evaluate horizontal transfer of PAs between donor and acceptor-plants by conducting a series of field trials using the PA-plant Lappula squarrosa as model and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…These conditions are real challenges, also recognized by the USP (United States Pharmacopeia) [ 149 ], and can help understand HSOS outbreaks from PAs in Ethiopia [ 68 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 ] and other subtropical and tropical countries [ 4 ]. The various facets of this fascinating PA concept, called horizontal natural product transfer, has been presented in publications since 2015 [ 137 ] und subsequently expanded [ 138 , 139 , 140 , 141 , 142 ], and is briefly summarized: (1) it was suggested that chemicals such as PAs may undergo translocation from a rotting PA-containing plant via soil into a nearby plant through uptake by its roots [ 137 ]; (2) the transfer of PAs was investigated using various herbs as acceptor plants, which had been mulched with dried plant material from the PA-containing Senecio jacobaea as providing plants, leading to high amounts of PAs in the nearby acceptor plants and confirming the horizontal transfer of PAs [ 142 ]; (3) the transfer occurs also from vital providing plants and is not limited to rotting plants, while the uptake by the roots of the acceptor plant proceeds through simple diffusion without an active transporter system, and, most importantly, the chemical imported may undergo modification in the acceptor plant [ 143 ]; (4) studies using co-cultures of the PA-containing Senecio jacobaea with parsley as an acceptor plant, which lacks its own PA biosynthesis, showed significant amounts of PAs in acceptor plants growing near the Senecio plants, of more than 200 μg/kg dry weight, previously synthesized by the Senecio donor plants [ 140 ]; and finally, (5) the uptake of PAs from the soil by the acceptor plant is variably determined by the rhizosphere pH, the concentration of protonated and unprotonated PAs in the soil, and the transpiration rate of the plant leaves [ 142 ].…”
Section: Uptake Of Pas By Plants From Contaminated Water and Soilmentioning
confidence: 97%
See 1 more Smart Citation
“…These conditions are real challenges, also recognized by the USP (United States Pharmacopeia) [ 149 ], and can help understand HSOS outbreaks from PAs in Ethiopia [ 68 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 ] and other subtropical and tropical countries [ 4 ]. The various facets of this fascinating PA concept, called horizontal natural product transfer, has been presented in publications since 2015 [ 137 ] und subsequently expanded [ 138 , 139 , 140 , 141 , 142 ], and is briefly summarized: (1) it was suggested that chemicals such as PAs may undergo translocation from a rotting PA-containing plant via soil into a nearby plant through uptake by its roots [ 137 ]; (2) the transfer of PAs was investigated using various herbs as acceptor plants, which had been mulched with dried plant material from the PA-containing Senecio jacobaea as providing plants, leading to high amounts of PAs in the nearby acceptor plants and confirming the horizontal transfer of PAs [ 142 ]; (3) the transfer occurs also from vital providing plants and is not limited to rotting plants, while the uptake by the roots of the acceptor plant proceeds through simple diffusion without an active transporter system, and, most importantly, the chemical imported may undergo modification in the acceptor plant [ 143 ]; (4) studies using co-cultures of the PA-containing Senecio jacobaea with parsley as an acceptor plant, which lacks its own PA biosynthesis, showed significant amounts of PAs in acceptor plants growing near the Senecio plants, of more than 200 μg/kg dry weight, previously synthesized by the Senecio donor plants [ 140 ]; and finally, (5) the uptake of PAs from the soil by the acceptor plant is variably determined by the rhizosphere pH, the concentration of protonated and unprotonated PAs in the soil, and the transpiration rate of the plant leaves [ 142 ].…”
Section: Uptake Of Pas By Plants From Contaminated Water and Soilmentioning
confidence: 97%
“…On theoretical grounds, there are two conditions, whereby plants can acquire PAs: first, plants biosynthesize PAs using chemical intermediates as precursors and enzymes catalyzing the synthesis [ 24 ], and second, those plants that primarily cannot synthesize and therefore do not contain PAs may acquire PAs through soil or water contaminated with PAs [ 137 , 138 , 139 , 140 , 141 , 142 ]. Despite these promising data supporting the new concept of horizontal natural product transfer of PAs [ 137 , 138 , 139 , 140 , 141 , 142 ], a recently published study questioned the relevance of this phenomenon for PAs under field conditions [ 143 ], although many reports provided enough evidence that that horizontal tranfer is well functioning under field conditions for PAs [ 130 , 136 ] and various compounds such as heavy metals [ 144 , 145 , 146 , 147 , 148 ]. Indeed, the uptake of toxins by plants is known for heavy metals found to be severely contaminating soil, for instance, the vegetable Ipomoea aquatica consumed by nearby villagers [ 144 ].…”
Section: Uptake Of Pas By Plants From Contaminated Water and Soilmentioning
confidence: 99%
“…They are present in food products such as cereals, honey, teas, herbal products, spices, and food supplements. Contamination can occur through direct or indirect contact [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…PAs are a class of phytotoxins that occur in an estimated 3% of flowering plants worldwide. More than 660 individual PAs and PANOs have been structurally characterized, and three plant families (Asteraceae, Boraginaceae, and Fabaceae) are among the most important sources of these toxins [1,2]. PA poisoning is caused by the consumption of herbal products containing these alkaloids for medicinal purposes or as culinary herbs.…”
Section: Introductionmentioning
confidence: 99%